Summary of CPWF Research in the Ganges River Basin - CGIAR Challenge Program on Water and Food (2014)
The CGIAR Challenge Program on Water and Food (CPWF) has worked in the Ganges River basin since 2003. From 2010 to 2014, its research for development activities focused on the southwest and south-central coastal zone of Bangladesh with some additional work in the coastal zone of West Bengal, India. In most polders the primary limiting factors are poor water management due to the lack of systematic operation of sluice gates; lack of separation of lands of varying elevations; and siltation of the irrigation and drainage canals within polders. Uncoordinated operation and delayed and/or inadequate maintenance of polder infrastructure remain common challenges throughout the coastal zone. Agricultural and aquacultural productivity and homestead food production have suffered as a result. Seizing the opportunity for change, CPWF set out to find ways to reduce poverty and improve social-ecological resilience in the coastal zone through improved water governance and management, and intensified and diversified agricultural and aquaculture systems.